IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGS) DESA DALAM UPAYA MEWUJUDKAN KEMANDIRIAN DESA PASAR BINANGA - Andre Chovado; Febri Yuliani; Iqbal Miftakhul Mujtahid (Media Bina Ilmiah, 2025)
The Implementation of the SDG program by the Village Government is carried out through the implementation of village development planning documents. The aim of this research is to analyze how the implementation of the SDG program in village development planning. Data analysis includes analysis of work plans, financial allocations, program implementation report and the impact of changes on social, economic and environmental aspects of the village. This research uses a qualitative method with an exploratory approach and data collection through interview techniques and documentation studies. The result of this research show that 14 of the 17 SDG programs have been implemented in Pasar Binanga Village through various infrastructure development programs, community empowerment and strengthening activities. There has been increase in the economy, health levels and sustainable use of the environment in Pasar Binanga Village. Community participation and the competence of the village head are the strongest factors in supporting the implementation of SDG policies in Pasar Binanga Village. However, obstacle to the policy implementation are the lack of empowerment program from the Regional Government and several central policies that are binding on village budget allocation obligations.